Japanese and Indonesian Relative Clausa Patterns - Ngurah Indra Pradhana (Diponegoro University, 2021)
In this research, the object of study is clause. This research is focused on the derivation of clauses known as relative clauses. In this study, it was examined about the differences and similarities in the formation patterns, meanings, and relation characteristics of clauses which are relatively good in two languages, namely between Japanese and Indonesian. The results of this research can be used in the teaching and learning process. As well as useful for readers and audiences who intend to pursue linguistics. The analytical method used in this research is the agih method. Based on the analysis that has been done, several conclusions can be drawn as follows. In Indonesian, a relative clause is indicated by the word